Control strategies to improve stability of LCC‐HVDC systems with multiple MMC taps. Issue 20 (8th October 2019) - Liu, Dalu; Kish, Gregory J.; Pirooz Azad, Sahar
Abstract : High‐voltage direct current (HVDC) is a proven technology for grid integration of renewable energy sources such as offshore wind farms and interconnecting distributed systems to main power grids. One economical solution for electrifying rural communities is to extract a small amount of power from existing HVDC transmission lines with power electronic converters, which is called tapping. This study analyses the feasibility and system performance of parallel tapping line‐commutated converter (LCC)‐HVDC systems with multiple full‐bridge modular multilevel converters under various fault scenarios and operating conditions. Simulation results reveal that undesirable system disturbances such as DC‐link voltage sags, DC‐link current overshoots, and the transient reduction of inverter extinction angle are imposed on the LCC‐HVDC system in the case of tap station AC side faults. Such disturbances would endanger the reliable operation of the entire LCC‐HVDC system with the parallel taps. Furthermore, this study proposes two fault mitigating schemes, i.e. a tap station current modulation controller and three supplementary controller configurations, to reduce the impact of tap station AC side faults on the LCC‐HVDC system. Both fault mitigating schemes are controller‐based solutions, which are augmented to the existing controllers by utilising only local measurements. The proposed schemes are verified through simulations in PSCAD/EMTDC.